Evaluasi Distribusi Energi Pada Alat Penghemat Energi Vertikal Untuk Penyempurnaan Produk Paten - Saputra, M. A. Ade; Alfarros, Muhammad Naufal; Adanta, Dendy (Jurnal Rekayasa Mesin, 2024)
This research aims to evaluate energy distribution in vertical energy saving devices in order to improve patented products. The method used includes measuring air flow speed, temperature and enthalpy at several points using an anemometer and digital thermometer. The fuel used is firewood, and the tool is tested with the help of an exhaust fan to draw in combustion gases. The test results show that the heat from the coal stove can be used to dry commodities placed on the shelves above, resulting in energy savings. The average speed of air flow at the exhaust site is 610 m/s, while the average outside air temperature is 285°C and the average exhaust air temperature is 591.4°C. Data analysis shows that the enthalpy values from the kiln to the disposal are irregular due to the inconsistent quality of the charcoal. Apart from that, there is wild air coming in through doors that are not tight enough. The conclusion of this research is that the use of vertical energy saving devices can save heat from coal stoves by utilizing this heat for drying other commodities. However, improvements need to be made to the tool design to reduce stray air entering and increase the consistency of combustion results.